The Impact of Investment Performance as a Moderator on Institutional Ownership, CSR, Investment Opportunity Set, and Firm Value - Vemas, Vinsensius; Afifah, Nur; Syahputri, Anggraini; Malini, Helma; Azazi, Anwar (Ilomata International Journal of Management, 2025)
Using investment performance as a moderator, this study seeks to ascertain how Institutional Ownership, Corporate Social Responsibility (CSR), and Investment Opportunity Set (IOS) influence the value of a firm. One significant factor that can explain whether a firm's state is favorable or unfavorable in the eyes of investors is its firm value. The percentage of institutional ownership, CSR disclosure, IOS, and investment performance are some elements that determine firm value. A quantitative strategy was used as the research methodology in this study. Secondary data from business sustainability and financial reports is used in the data collection. Purposive sampling was employed to collect research data from companies in the energy and mineral sector listed on the Indonesia Stock Exchange during 2019–2023. SPSS 25 and Eviews 12 software were utilized for data processing, while multiple regression model analysis and the traditional assumption test were used for testing. The study's results suggest that IOS significantly increases business value, while institutional ownership and corporate social responsibility (CSR) have a positive but minimal impact. When Investment Performance moderates CSR, it has a negative and insignificant effect on Firm Value. Conversely, Institutional Ownership and IOS, which Investment Performance regulates, exhibit a substantial positive impact.